Ethical perspectives on the Manguni bird: Integrating nature, humanity, and divine connection - Rencan C. Marbun (HTS Teologiese Studies/Theological Studies)
The Manguni bird plays a central role in the cosmology of the Minahasa people as a symbol of nature, society and spirituality. In Minahasa tradition, the Manguni is not only regarded as a natural sign that provides clues about the good or bad nature of an event but also as a divine intermediary that brings messages from God (Opo Empung). Furthermore, Manguni serves as a social symbol that strengthens the cohesion of the Minahasa community, connecting humans, nature and God in spiritual harmony. This article discusses the role of Manguni in three aspects: as an ecological sign reflecting harmony with the environment, as a social bond representing the collective identity of Minahasa and as a medium that communicates divine messages. The article also highlights the importance of integrating ecology into contextual Christian theology, especially in regions rich in local cultural traditions.